Overcoming obstacles: the impact of harassment on women's motivation to pursue solo women travel - Surya Laksana Rahjasa; Putu Wiwekananda; I Gusti Agung Andika Surya Finardi (Universitas Merdeka Malang, 2024)
This research aims to explore the experiences and motivations of women who practice solo women travel, as well as the impact of the harassment they experience on their desire to continue the practice of solo women travel or not. Solo women travel has become a trend in the world of tourism which has been increasing in recent years. Their motivation for practicing solo women travel is to seek identity, freedom and self-empowerment. However, solo women travel often face the risk of sexual and racial harassment which can cause fear, anxiety, trauma and influence their desire to continue the practice of solo women travel or not. This research uses qualitative methods with in-depth interview techniques with women who are categorized as solo women travel. The research results show that although harassment is a threat to solo women travel, many women continue the practice of solo women travel by adopting preventive measures. In conclusion, harassment does not completely affect a solo woman travel motivation to travel alone.